What is Ethical Competence? The Role of Empathy, Personal Values, and the Five-Factor Model of Personality in Ethical Decision-Making - Pohling, Rico (Journal of business ethics, 2016)
The objective of the present research was two-fold: (1) to provide a new definition of ethical competence, and (2) to clarify the influence of empathy, personal values, and the five-factor model of personality on ethical competence. The present research provides a comprehensive overview about recent approaches and empirically explores the interconnections of these constructs. 366 German undergraduate students were examined in a cross-sectional study that investigated the relationship of empathy, personal values, and the five-factor model of personality with moral judgment competence and counterproductive work behavior as indicators of moral judgment and behavior. We found self-transcendence values to be related to both, high levels of empathy and ethical competence, in contrast to self-enhancement values. Multiple mediation analysis revealed unique effects of empathy on ethical competence through values as mediators. Affective (but not cognitive) empathy transmitted its effect on ethical competence through benevolence, conformity, tradition, power, and hedonism. Most importantly, perspective taking lost its predictive power when investigated alongside affective empathy dimensions. These results converge to an important role of affective empathy, in particular empathic concern, with regard to personal values and ethical competence. Furthermore, the five-factor model of personality explained variance in measures of ethical competence. Our research suggests that organizational decision makers should consider the role of empathy, personal values, and the five-factor model in their human resource management in order to select employees with high ethical competence.